Open Multimirror Resonator with Echelette Mirror - A.I. Fisun; O.N. Sukhoruchko; V.K. Korneenkov; V.G. Dudka; O.I. Belous (Журнал нано- та електронної фізики)
E-polarized oscillations in open multimirror resonator have been investigated. One of the mirrors of the open resonator is defined as an echelette grating with equal steps. Spectra and field topology of the E-polarized oscillations of resonator are derived theoretically and experimentally at 8 mm wave band.